Evaluation of the duration of motor and sensory blockade in cats submitted to epidural anesthesia with ropivacaine alone and associated with tramadol. - Corrêa, C. B. S; Moraes, S. F. S.; Conceição, E. D. V (Scientific Electronic Archives, 2018)
Currently, epidural anesthesia is widely used in veterinary medicine, this is mainly due to its ease and relative safety. The objective of this study was to compare the duration of motor and sensory blockade in epidural anaesthetized cats with ropivacaine alone and associated with tramadol submitted to elective ovariossalpingohisterectomy (OSH) at the Veterinary Hospital, located in the municipality of Sinop, Mato Grosso. Sixteen animals, pre-medicated with chlorpromazine and fentanyl, were used with ketamine and diazepam, followed by administration of the drugs under study by the epidural route and general inhalation anesthesia maintained with isoflurane. They were randomly assigned to two groups of 8 animals; Group A was administered epidurally, ropivacaine; and in Group B the tramadol-associated ropivacaine was used in a total volume of 4.5 ml / kg. The following were evaluated: cardiac waves, heart and respiratory rates, rectal temperature and the intensity and duration of sensory and motor blockade.